Memaknai Istilah Antikristus dalam Surat-surat Yohanes dan Penerapannya dalam Menghadapi Ajaran Palsu pada Masa Kini - Arnolis Ratupaira (Sekolah Tinggi Alkitab Jember, 2024)
The letters of John are significant in understanding the concept of the antichrist, as they reveal how the antichrist refers to false teachers, including liars and deceivers. These individuals have separated themselves from the original group of believers and have embraced false teachings. This study addresses the challenge believers face in interpreting the term